Menakar Resolusi Konflik di Dunia Islam - Surwandono, Surwandono (Jurnal Hubungan Internasional, 2012)
Islamic history has shown that Islam was born in a state of conflict which acute, both local and international levels. Thus, itâs really important to explore the structure of Islamic values which very appreciative with the spirit of âpeace, security, fully-accepted, obeyâ as defined in the word Islam itself. This paper argues that the history of Muhammad prophet leadership gave a clear lesson about how Islamic perspectives in resolving conflict of various levels:community, country, and in the arena of International relations.